The European Union and Europe's New Regionalism The Challenge of Enlargement, Neighborhood, and Globalization - Stefanova, Boyka M. (Springer International Publishing, 2018)
This book presents a new approach to studying the European Union's regional and global relevance. It recasts into a dynamic perspective the three most significant systemic processes that define the EU as a regionalist project: its enlargement, neighborhood, and mega-regional policies. The book argues that these processes collectively demonstrate a dynamic shift of the core tenets of European regionalism from an inward-looking process of region building to an open, selective system of global interactions. Boyka M. Stefanova is Associate Professor in the Department of Political Science and Geography at the University of Texas at San Antonio, USA.